Empire and dissent the United States and Latin America (American encounters, global interactions, 2008)
"Since the early nineteenth century, the United States has repeatedly intervened in the affairs of Latin American nations to pursue its own interests and to protect those countries from other imperial powers or from internal threats. The resentment and opposition generated by the encroachment of U.S. power has been evident in the recurrent attempts of Latin American nations to pull away from U.S. dominance and in the frequent appearance of popular discontent and unrest directed against imperialist U.S. policies. In Empire and Dissent, senior Latin Americanists explore the interplay between various dimensions of imperial power and the resulting dissent and resistance. Several essays provide historical perspective on contemporary U.S.-hemispheric relations. These include an analysis of the nature and dynamics of imperial domination, an assessment of financial relations between the United States and Latin America since the end of World War II, an account of Native American resistance to colonialism, and a consideration of the British government's decision to abolish slavery in its colonies. Other essays focus on present-day conflicts in the Americas, highlighting various modes of domination and dissent, resistance and accommodation. Examining southern Mexico's Zapatista movement, one contributor discusses dissent in the era of globalization. Other contributors investigate the surprisingly conventional economic policies of Brazil's president, Luiz Inacio Lula da Silva; Argentina's recovery from its massive 2001 debt default; the role of coca markets in the election of Bolivia's first indigenous president, Evo Morales; and the possibilities for extensive social change in Venezuela. A readers' guide offers a timeline of key events from 1823 through 2007, along with a list of important individuals, institutions, and places." -- Publisher's description.